The association of neutrophil-to-lymphocyte ratio with post-chemotherapy pulmonary infection in lung cancer patients - Tao Sun; Xiaobo He; Jun Liu (Frontiers in Medicine)
BackgroundLung cancer patients are particularly vulnerable to pulmonary infections following chemotherapy, which can lead to suboptimal treatment outcomes and increased mortality rates. The neutrophil-to-lymphocyte ratio (NLR), an established inflammatory marker, has been extensively studied; however, its diagnostic value in identifying post-chemotherapy pulmonary infection (PCPI) in lung cancer patients remains unclear. This study aims to evaluate the independent diagnostic effectiveness of NLR in detecting PCPI among lung cancer patients.MethodsA retrospective analysis was performed on clinical data from 638 lung cancer patients who underwent chemotherapy at the Central Hospital of Shaoyang between January 2020 and December 2023. After excluding cases with incomplete data, 502 patients were included in the final analysis. Due to the low incidence of PCPI within this cohort (19.52%), the Synthetic Minority Over-sampling Technique (SMOTE) was utilized to achieve data balance. Both the balanced and unbalanced datasets were subsequently analyzed and validated using multivariable regression analysis, restricted cubic spline (RCS) analysis, subgroup analysis, and sensitivity analysis.ResultsThe findings demonstrated that NLR serves as an independent risk factor for PCPI in patients with lung cancer, irrespective of dataset balance [balanced dataset: odds ratio (OR) = 1.12, 95% confidence interval (CI): 1.08–1.16; unbalanced dataset: OR = 1.08, 95% CI: 1.03–1.13]. Furthermore, in the balanced dataset, after adjusting for all covariates (Model 4), quartile analysis of NLR revealed a significant increase in the risk of PCPI with higher NLR levels (fourth quartile group OR = 5.64, 95% CI: 3.17–10.01, p < 0.001). The RCS analysis corroborated the nonlinear association between NLR and PCPI. Subgroup analysis revealed that within the chemotherapy regimen subgroups, the association between NLR and PCPI was significantly higher in patients receiving platinum-based chemotherapy (PBC) compared to those receiving non-platinum-based chemotherapy (NPBC) (p for interaction = 0.001). Sensitivity analyses further affirmed the robustness of the model outcomes.ConclusionThe analysis in this study indicates that NLR has the potential to be a predictor of PCPI for lung cancer patients. Although these preliminary research findings demonstrate diagnostic promise, its clinical applicability still needs to be verified through multicenter prospective studies to provide reliable evidence for decision-making.